Aspek perkembangan anak usia dini di Taman Kanak-Kanak - Sanati, Alfi; Rizkita Putri, Farah (STAI Syekh Jangkung, 2026)
ABSTRACT This study aims to support the optimal development of 5-year-old children in Group A of Nurul Ikhsan Beketel Kindergarten. Observed development encompassed physical-motor, cognitive, socio-emotional, language, and religious values ​​and character. The approach used was a combination of participant observation and a qualitative descriptive case study, involving all children in Group A during the research period, from December 4 to December 18, 2025. Data collection was conducted through direct observation, field notes, and assessments based on an early childhood development rubric. The results showed that most children had achieved the expected developmental standards in each aspect. In the physical-motor aspect, gross and fine motor coordination showed good progress for their age. Children's cognitive development demonstrated simple problem-solving abilities, recognition of number and color concepts, and creativity developed through play and exploration. The socio-emotional aspect demonstrated children's ability to interact with peers, follow play rules, and manage basic emotions well. Language development was reflected in the ability to speak clearly, understand instructions, and demonstrate a strong interest in listening to stories and expressing ideas. Religious and character values ​​are also well internalized through daily activities and integrated learning. The implementation of learning that prioritizes a holistic approach has proven effective in supporting children's comprehensive development. These findings indicate that with the right support through a conducive learning environment and appropriate teaching methods, 5-year-old children can achieve optimal development in all aspects. Keywords: early childhood development, Group A, Nurul Ikhsan Beketel Kindergarten, observation, holistic learning, character education.